Evidence for a Bs0 π± State - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2016)
We report evidence for a narrow structure, X(5568), in the decay sequence X(5568)→Bs0π±, Bs0→J/ψφ, J/ψ→μ+μ-, φ→K+K-. This is evidence for the first instance of a hadronic state with valence quarks of four different flavors. The mass and natural width of this state are measured to be m=5567.8±2.9(stat)-1.9+0.9(syst) MeV/c2 and Γ=21.9±6.4(stat)-2.5+5.0(syst) MeV/c2. If the decay is X(5568)→Bs∗π±→Bs0γπ± with an unseen γ, m(X(5568)) will be shifted up by m(Bs∗)-m(Bs0)∼49 MeV/c2. This measurement is based on 10.4 fb-1 of pp collision data at s=1.96 TeV collected by the D0 experiment at the Fermilab Tevatron collider.